Allocation Method for Mobile Charging Vehicles Based on the Spatial Charging Demand - Yujun, Liu; Hongyuan, Yin; Pingliang, Zeng; Zhongdong, Wang; Zigang, Lu (Elektronika ir Elektrotechnika, 2018)
At present, the development of electric vehicles (EV) is limited by the lack of charging facilities. While the construction of charging stations is slowing down because of the small ownership of EV and the high operational cost. The mobile charging vehicles (MCV) are proposed to replace the charging station. At first, this paper introduces the MCV’s operation architecture. Then the spatial charging demand is estimated based on the travel chain. At last, the allocation method of mobile charging vehicles is studied in detail with the result of estimation result. The simulation result shows that proper number of MCV can replace the function of charging station as well as meet the needs of charging services.DOI: http://dx.doi.org/10.5755/j01.eie.24.1.20153